Clinical and Genomic Analysis of Liver Abscess-Causing Klebsiella pneumoniae Identifies New Liver Abscess-Associated Virulence Genes - Ye, Meiping; Tu, Jianfei; Jiang, Jianping; Bi, Yingmin; You, Weibo; Zhang, Yanliang; Ren, Jianmin; Zhu, Taohui; Cao, Zhuo; Yu, Zuochun; Shao, Chuxiao; Shen, Zhen; et al. (Frontiers in Cellular and Infection Microbiology, 2016)
Hypervirulent variants of Klebsiella pneumoniae (hvKp) that cause invasive community-acquired pyogenic liver abscess have emerged globally. Little is known about the virulence determinants associated with hvKp, except for the virulence genes rmpA/A2 and siderophores (iroBCD/iucABCD) carried by the pK2044-like large virulence plasmid. Here, we collected most recent clinical isolates of hvKp from pyogenic liver abscess (PLA) samples in China, and performed clinical, molecular, and genomic sequencing analyses. We found that 90.9% (40/44) of the pathogens causing PLA were K. pneumoniae. Among the 40 LA-Kp, K1 (62.5%) and K2 (17.5%) were the dominant serotypes, and ST23 (47.5%) was the major sequence type. S1-PFGE analyses demonstrated that although 77.5% (31/40) of the LA-Kp isolates harbored a single large virulence plasmid varied in size, 5 (12.5%) isolates had no plasmid and 4 (10%) had two or three plasmids. Whole genome sequencing and comparative analysis of 3 LA-Kp and 3 non-LA-Kp identified 133 genes present only in LA-Kp. Further, large scale screening of the 133 genes in 45 LA-Kp and 103 non-LA-Kp genome sequences from public databases identified 30 genes that were highly associated with LA-Kp, including iroBCD, iucABCD and rmpA/A2 and 21 new genes. Then, these 21 new genes were analyzed in 40 LA-Kp and 86 non-LA-Kp clinical isolates collected in this study by PCR, showing that new genes were present 80-100% among LA-Kp isolates while 2-11% in K. pneumoniae isolates from sputum and urine. Several of the 21 genes have been proposed as virulence factors in other bacteria, such as the gene encoding SAM-dependent methyltransferase and pagO which protects bacteria from phagocytosis. Taken together, these genes are likely new virulence factors contributing to the hypervirulence phenotype of hvKp, and may deepen our understanding of virulence mechanism of hvKp.